2016
DOI: 10.1017/s0021859616001015
|View full text |Cite
|
Sign up to set email alerts
|

Applying the generalized additive main effects and multiplicative interaction model to analysis of maize genotypes resistant to grey leaf spot

Abstract: SUMMARYAnalysing the stability and adaptation of cultivars to different environments is always necessary before recommending them for planting on large areas. Additive main effects and multiplicative interaction (AMMI) models have been used to analyse genotype-by-environment interactions (G × E). AMMI models require data with homogeneous variance, normal errors and additive effects. However, agronomic data do not always conform to these statistical assumptions. The objective of the present study was to analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For example, G × E interaction analyses have been performed in contrasting oilseed rape growing regions in Canada, Finland, Poland, Turkey, Iran, Pakistan, China and Australia (Brandle and McVetty, 1988; Peltonen-Sainio and Jauhiainen, 2008; Moghaddam and Pourdad, 2011; Pilarczyk, 2013; Tahira et al ., 2013; Zhang et al ., 2013, 2017; Mortazavian and Azizi-Nia, 2014; Nowosad et al ., 2016; He et al ., 2017). In South America, G × E analyses have been conducted previously for sunflower, soybean and maize yields (de la Vega et al ., 2001; Dardanelli et al ., 2006; Acorsi et al ., 2017), but for oilseed rape, G × E analysis has been limited to the Southeast of the Pampas Region (Takashima et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, G × E interaction analyses have been performed in contrasting oilseed rape growing regions in Canada, Finland, Poland, Turkey, Iran, Pakistan, China and Australia (Brandle and McVetty, 1988; Peltonen-Sainio and Jauhiainen, 2008; Moghaddam and Pourdad, 2011; Pilarczyk, 2013; Tahira et al ., 2013; Zhang et al ., 2013, 2017; Mortazavian and Azizi-Nia, 2014; Nowosad et al ., 2016; He et al ., 2017). In South America, G × E analyses have been conducted previously for sunflower, soybean and maize yields (de la Vega et al ., 2001; Dardanelli et al ., 2006; Acorsi et al ., 2017), but for oilseed rape, G × E analysis has been limited to the Southeast of the Pampas Region (Takashima et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid growth allowed plants to abstain from the systemic disease to some extent. Recently, GGE biplot has been used to characterize and determine stability of germplasm, breeding lines and cultivars resistance to diseases such as anthracnose in water yam (Egesi et al ., 2009), chocolate spot disease in faba bean (Villegas et al ., 2009), white rust in brassica (Sandhu et al ., 2015), dry root rot and stunt disease in chickpea (Kumar et al ., 2017), yellow mosaic disease in mungbean (Parihar et al ., 2017), grey leaf spot in maize (Acorsi et al ., 2017). When the first section of the biplot was assessed separately from the entire graph, it was observed that 19 pure lines were placed in this section (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GGE biplot usually used to (i) evaluate whichwon-where pattern, (ii) investigate mega environment, (iii) determine mean performance and stability of genotypes in multi environment yield trials (Yan and Falk, 2002). Lately, GGE biplot has been used to characterize and determine stability of germplasm, breeding lines and cultivars resistance to diseases such as anthracnose in water yam (Egesi et al, 2009), chocolate spot disease in faba bean (Villegas-Fernandez et al, 2009), white rust in Brassica (Sandhu et al, 2015), Fusarium udum in pigeonpea (Sharma et al, 2016), dry root rot an stunt disease in chickpea (Kumar et al, 2017), yellow mosaic disease in mungbean (Parihar et al, 2017), grey leaf spot in maize (Acorsi et al, 2017) grain yields of maize hybrids (Ilker et al, 2009;Mitrović et al, 2012). Leaf rust, (caused by Puccinia triticina) is encountered in wheat cultivation growing areas in coastal regions, Southeastern Anatolia, Çukurova, Middle Black Sea, Southern Marmara and Thrace regions of Turkey.…”
Section: Introductionmentioning
confidence: 99%